2019
DOI: 10.1113/jp277617
|View full text |Cite
|
Sign up to set email alerts
|

Cholinergic neurons in the pedunculopontine tegmental nucleus modulate breathing in rats by direct projections to the retrotrapezoid nucleus

Abstract: Key points Cholinergic projections from the pedunculopontine tegmental nucleus (PPTg) to the retrotrapezoid nucleus (RTN) are considered to be important for sleep–wake state‐dependent control of breathing. The RTN also receives cholinergic input from the postinspiratory complex. Stimulation of the PPTg increases respiratory output under control conditions but not when muscarinic receptors in the RTN are blocked. The data obtained in the present study support the possibility that arousal‐dependent modulation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 55 publications
0
16
0
Order By: Relevance
“…Although PPN-DBS is primarily used to improve gait freezing and postural instability in PD and primary progressive freezing of gait (PPFG), it also shows a modulation effect on some non-motor functions, including REM sleep, mood, attention, arousal, sleep-wake cycle and cognition [ 164 - 167 ]. Recent studies have demonstrated PPN is involved in sleep–wake state-dependent central breathing regulation through cholinergic projections to the retrotrapezoid nucleus, which indicates PPN as a potential target for improving SDB in PD patients [ 168 , 169 ]. However, there are also some studies that suggest PPN-DBS may contribute to REM sleep atonia and aggravate RBD in PD patients [ 165 ].…”
Section: Non-pharmacological Treatmentsmentioning
confidence: 99%
“…Although PPN-DBS is primarily used to improve gait freezing and postural instability in PD and primary progressive freezing of gait (PPFG), it also shows a modulation effect on some non-motor functions, including REM sleep, mood, attention, arousal, sleep-wake cycle and cognition [ 164 - 167 ]. Recent studies have demonstrated PPN is involved in sleep–wake state-dependent central breathing regulation through cholinergic projections to the retrotrapezoid nucleus, which indicates PPN as a potential target for improving SDB in PD patients [ 168 , 169 ]. However, there are also some studies that suggest PPN-DBS may contribute to REM sleep atonia and aggravate RBD in PD patients [ 165 ].…”
Section: Non-pharmacological Treatmentsmentioning
confidence: 99%
“…Cholinergic neurons in the pedunculopontine tegmental nucleus (PPT), which project widely throughout the reticular formation (RF), and show state‐dependent activity were hypothesized as a likely source for the recruitment of active expiration in REM sleep (Jones, 1990; Topchiy, Waxman, Radulovacki, & Carley, 2010; Woolf, 1991; Woolf & Butcher, 1989; Yeomans, 2012). However, recent tracing studies aiming to identify a further rostral location in the pF L area failed to show any connection between the pF L and PPT (Lima et al, 2019; Silva, Oliveira, Souza, Moreira, & Takakura, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The cholinergic system is involved in respiratory control, including central chemosensitivity, state-dependent modulation of breathing, and respiratory motor output [ 34 , 35 , 36 , 37 ]. The retrotrapezoid nucleus (RTN) contributing to chemical respiratory drive (CO 2 /H + ) [ 38 ] receives cholinergic input from the post-inspiratory complex (PiCO) and pedunculopontine tegmental nucleus (PPTg), and stimulation of PPTg has been shown to increase respiratory activity, in part, by cholinergic activation of chemosensitive RTN [ 36 ]. In addition, cholinergic innervation is also present in the parafacial respiratory group (pFRG) where muscarinic transmission contributes to neuronal excitation and promotes recruitment of abdominal muscles and active expiratory flow [ 35 ].…”
Section: Discussionmentioning
confidence: 99%